2005
DOI: 10.3183/npprj-2005-20-03-p270-276
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymeric multilayers of starch onto wood fibres to enhance strength properties of paper

Abstract: SUMMARY:Polyelectrolyte multilayers of cationic and anionic starch have been used to enhance the strength properties of paper. All starches used in this investigation had a degree of substitution around 0.065. Optical reflectometry showed that a combination of cationic and anionic starch could form polyelectrolyte multilayers onto silicon oxide surfaces. The same combination of starches was then applied to unbeaten, bleached softwood kraft fibres to form three layers, i.e. a cationic-/anionic/cationic starch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…When the adding amount of β-CD-CSCipHCl was 2.5%, the tensile and tear index were increased 36.8% and 9.0%, respectively. It is believed that β-CD-CS-CipHCl adsorbs to cellulosic fibers during wet end processing, thereby enhancing bonding strength between the fibers during the process of sheet forming (Eriksson et al 2005;Hubbe 2007). It is well known that the adsorption of CS on fibers will reach a saturation condition and any further increase of the adsorption amount beyond the saturation point is impossible.…”
Section: Physical Properties Of the Prepared Paper Sheets Loaded Withmentioning
confidence: 99%
“…When the adding amount of β-CD-CSCipHCl was 2.5%, the tensile and tear index were increased 36.8% and 9.0%, respectively. It is believed that β-CD-CS-CipHCl adsorbs to cellulosic fibers during wet end processing, thereby enhancing bonding strength between the fibers during the process of sheet forming (Eriksson et al 2005;Hubbe 2007). It is well known that the adsorption of CS on fibers will reach a saturation condition and any further increase of the adsorption amount beyond the saturation point is impossible.…”
Section: Physical Properties Of the Prepared Paper Sheets Loaded Withmentioning
confidence: 99%
“…Most starches consist of about 70% amylopectin and 30% of hot water soluble amylose. However, there are source-dependent differences and these will influence the properties of the starch as adhesive , Eriksson et al 2005. In spite of this, a common problem with starch-based adhesives is a reduced water-resistance of the products (Basta et al 2005, Dix 2006see below).…”
Section: Adhesives From Cellulose Hemicellulose Starch Dextrins Amentioning
confidence: 99%
“…The first practical application aimed at adsorbing high amounts of cationic PAE (polyamideamine epichlorohydrine), a common wet strength additive, to improve wet strength in tissue paper by combining the PAE treatment with a carboxymethylcellulose CMC treatment (Sandberg and Andreasson 2000). Later work along these lines has also shown that the structure of the multilayers (Eriksson et al, 2005a, Notley et al, 2005 as well as the chemical structure of the used chemicals (Eriksson et al 2005b) have a large influence on the strength-enhancing properties. PEMs of cationic amylose and anionic potato starch were also shown to be much more efficient than conventional PEMs of conventional cationic and anionic potato starch (Eriksson et al 2005b).…”
mentioning
confidence: 99%
“…Later work along these lines has also shown that the structure of the multilayers (Eriksson et al, 2005a, Notley et al, 2005 as well as the chemical structure of the used chemicals (Eriksson et al 2005b) have a large influence on the strength-enhancing properties. PEMs of cationic amylose and anionic potato starch were also shown to be much more efficient than conventional PEMs of conventional cationic and anionic potato starch (Eriksson et al 2005b). In Notley et al (2005) it was furthermore shown that a high mobility of the polyelectrolyte multilayer was important to create a strong fibre/fibre joint.…”
mentioning
confidence: 99%